(untitled) (Journal of Computational Mathematics, 2018)
This paper is concerned with the convergence of multigrid methods (MGM) on nonsymmetric elliptic variational inequalities. On the basis of Wang and Zeng's work (1988), we develop the convergence results of the smoothing operator (i.e. PJOR and PSOR). We also extend the multigrid method of J.Mandel (1984) to nonsymmetric variational inequalities and obtain the convergence of MGM for these problems.